Aspectos da ciência na literatura: a pólvora e o salitre em Memorial de Maria Moura de Rachel de Queiroz - Soares, Maria Milza de Farias (2010)
This work discusses the aspects of Science in the Literatura, through the novel Memorial de Maria Moura, by Rachel de Queiroz. In this case study, the use of the gunpowder (a valuable material used in the 19th century) and its components is highlighted. Among its components mentioned by the author on her work, she emphasizes the saltpeter as well as the way to transport it avoiding its waste. It is known that Ceara, the setting where the narrative takes place, was also the place where the gunpowder was produced. In Ceara, there were mines for the extraction of the saltpeter and laboratories for refining it. Rachel de Queiroz visits the 19th century, writing the novel based on the technique and in the historical context of the period